2017
DOI: 10.1063/1.4989925
|View full text |Cite
|
Sign up to set email alerts
|

Highly accurate intensity factors of pure CO2 lines near 2 μm

Abstract: Line intensities for carbon dioxide are measured with a novel spectroscopic approach, assisted by an optical frequency comb synthesizer for frequency calibration purposes. The main feature of the spectrometer consists in the exploitation of optical feedback from a V-shaped high-finesse optical resonator to effectively narrow a distributed feedback diode laser at the wavelength of 2 μm. Laser-gas interaction takes place inside an isothermal cell, which is placed on the transmission from the cavity. High quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…There are several methods for determining the line intensity. Data are usually analysed by fitting the peak area of a normalised line profile to the measured spectrum [159,160]. Line intensity determinations from multiple spectroscopic observations can also be analysed and combined by global fits of semi-classical, effective dipole moment surfaces (DMSs) [161].…”
Section: Cavity Ring-down Spectroscopy and Off Axis Integrated-cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods for determining the line intensity. Data are usually analysed by fitting the peak area of a normalised line profile to the measured spectrum [159,160]. Line intensity determinations from multiple spectroscopic observations can also be analysed and combined by global fits of semi-classical, effective dipole moment surfaces (DMSs) [161].…”
Section: Cavity Ring-down Spectroscopy and Off Axis Integrated-cavitymentioning
confidence: 99%
“…Accurate measurements have also been reported using other techniques including traditional FTIR (see section 4.4), and direct TDLAS (see section 4.3) and cavity-enhanced laser spectroscopy methods. Importantly, these measurements now provide the most stringent tests of ab initio calculations which are contributing to spectroscopic line lists [159,165,171].…”
Section: Cavity Ring-down Spectroscopy and Off Axis Integrated-cavitymentioning
confidence: 99%
“…It was shown that this profile can model measured transitions of various molecular systems to within a few 0.1 % (e.g. [5][6][7][8][9][10][11][12][13]). The international spectroscopic database HITRAN [14] now provides parameters of this profile when available.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this profile can model measured spectra of various molecular systems to within a few 0.1 % (e.g. [15][16][17][18][19][20][21][22][23] ). The international spectroscopic database HITRAN 24 now provides parameters for this profile when available.…”
Section: Introductionmentioning
confidence: 99%